Peranan Keuangan Berkelanjutan Pada Industri Perbankan Dalam Mendukung Sustainable Development Goals: Peranan Keuangan Berkelanjutan Pada Industri Perbankan Dalam Mendukung Sustainable Development Goals - Neneng Hayati; Erwin Yulianto; Syafdinal . (Universitas Widyatama, 2020)
The role of sustainable finance in the Banking Industry at this time was initiated by the Financial Services Authority (OJK) and World Wildlife Funding (WWF) in targeting economic growth so that negative impacts arise from the process of economic development. This encourages environmentalists, companies and national and global governments to trigger a sustainable development that prioritizes harmony in economic, environmental and social aspects. OJK has collaborated with financial institutions to develop a Sustainable Finance Road Map with the aim of describing the conditions to be achieved regarding sustainable finance in Indonesia in the 2015-2024 period for the financial services industry. This initiative was also built to contribute while capturing business opportunities for Indonesia's economic development efforts that are resilient to climate change and contribute directly to efforts to achieve the Sustainable Development Goals (SDGs). The analysis method used is descriptive qualitative where the data collection technique in this study uses online data search. Based on the road map prepared by the OJK, banks in Indonesia have committed to the Sustainable Finance Action Plan (RAKB) to provide credit to creditors who have certification in accordance with the principles of Environmental, Social and Governance (LST) and AMDAL permits (Environmental Impact Analysis ) in the green construction, agriculture, green infrastructure, forestry, renewable energy, recycling and energy efficiency sectors